Organizational Culture And Hospital Service Quality: A Mixed-Methods Research In Indonesian Private Hospital - Dominika Lepan Tukan; Emiliana Tarigan; Agustinus Bandur (Syntax Literate, 2023)
The purpose of this study is to examine and explore how organizational culture with four cultural patterns (internal process, rational goal, open system, human relations) affects the quality of service at X hospital, Bandung. This study uses a Mixed Methods design. The subjects of this study are 207 respondents as well as participants consisting of 124 respondents and hospital employees, 80 respondents and patient participants. Data are collected using questionnaires and open-ended questions. Cosstab test is used to analyze quantitative data, while thematic analysis and corss-case analysis are used to analyze qualitative data. The results of the quantitative data analysis show that organizational culture has a significant effect towards service quality at X Hospital, Bandung. This result is strengthened by the analysis of qualitative studies which states that organizational culture is oriented towards service quality. This study has proven that organizational culture can improve the quality of service aimed at a significant positive difference in service quality between patients and hospital employees.